Communicative Strategies of the Representation of Implicit Meaning (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the communicative strategies employed to represent implicit meaning in discourse. Implicit meaning refers to the unspoken or indirectly conveyed content of an utterance, which is inferred by the interlocutor through context, background knowledge, and shared cognitive environments. Drawing on Grice’s theory of implicature and contemporary pragmatic models, the study identifies key communicative strategies such as presupposition, inference, ellipsis, metaphor, and contextual signaling. The findings suggest that these strategies are fundamental to effective communication, allowing speakers to convey complex meanings economically and subtly. The paper emphasizes the cognitive and cultural dimensions of implicit meaning and the necessity of strategic discourse planning to ensure successful communication.